ALGORITHMS OF SIMULATION OF TECHNICAL SERVICE PROCESSES AS COMPLEX RADIOELECTRONIC OBJECTS - Zhyrov G. В.; Lenkov, E. S. (Radio Electronics, Computer Science, Control, 2018)
Context. Development of complex radioelectronic facilities and maintenance is impossible without the development of models and software, to optimize these processes. For this, the corresponding algorithms have been developed in the work, which are part of the software, which is an urgent task. Objective. The purpose of this work is to develop approaches to improve the reliability of the object and reduce the cost of its operation based on the use of simulation statistical modeling. Method. The method of investigation is based on the idea that the technical state of an object is determined by the technical state of its elements, and the concept of a determining parameter is used to determine the technical state of an element. The value of the parameter can be controlled by means of diagnostics. As the models of element failures, a DN-distribution is used. Results. The developed algorithms are an integral part of the simulation statistical model of the object. The simulation allows to determine the optimal design characteristics of the object and the parameters of its maintenance, and the criterion is to maximize reliability indicators and minimize the cost of operating the facility. Conclusions. The scientific novelty of the work is to improve the state maintenance algorithms, which, unlike the existing ones, use the predictive parameter of the average degradation rate of the element’s determining parameter based on the three-parameter exponential smoothing model. Practical value consists in the development of algorithms that form the basis of software that implements the process of determining reliability indicators and the cost of operating an object of radioelectronic equipment from the structural composition of the facility itself and the parameters of maintenance.